Advanced cleaning products formulations database - Flick, Ernest W. (William Andrew Pub., 2006)
This database includes: "Formulation in the cleaning product industry undergoes constant change due to raw material increases and environmental considerations. The well-known and consulted formulation books compiled by Ernest Flick are now made available in a database for the first time. In addition, at least 700 new formulations have been added so that approximately 3700 entries are included."-- William Andrew Publishing web site (viewed on May 3, 2007).
Title from disc surface.
Keywords: Cleaning compounds -- Databases.; elektronické knihy; electronic books